Neoadjuvant immune checkpoint inhibition in the management of glioblastoma: Exploring a new frontier - Frederico, Stephen C.; Darling, Corbin; Bielanin, John P.; Dubinsky, Alexandra C.; Zhang, Xiaoran; Hadjipanayis, Constantinos G.; Kohanbash, Gary (Frontiers in Immunology, 2023)
Brain tumors are one of the leading causes of cancer related death in both the adult and pediatric patient population. Gliomas represent a cohort of brain tumors derived from glial cell lineages which include astrocytomas, oligodendrogliomas and ependymomas. These tumors are known to grow aggressively and have a high lethality with high grade astrocytomas being the most aggressive tumor in this group. Currently, few treatment options exist for malignant gliomas outside of surgical resection, radiation therapy and chemotherapy. While these measures have been shown to marginally improve patient survival, patients, especially those diagnosed with high grade astrocytomas, often experience a recurrence of their disease. Following disease recurrence, treatment options become more limited as additional surgical resections can pose life threatening risk to the patient, patients may be ineligible for additional radiation, and the recurrent tumor may be resistant to chemotherapy. Immune checkpoint inhibitors have revolutionized the field of cancer immunotherapy as many patients with cancers residing outside the central nervous system have experienced a survival benefit from this treatment modality. It has often been observed that this survival benefit is increased following neoadjuvant administration of immune checkpoint inhibitors as tumor antigen is still present in the patient which enables a more robust anti-tumor immune response. Interestingly, results for immune checkpoint inhibitor-based studies for patients with gliomas have been largely disappointing which is a stark contrast from the success this treatment modality has had in non-central nervous system cancers. In this review we will discuss the various benefits of neoadjuvant immune checkpoint inhibition such as how this approach reduces tumor burden and allows for a greater induction of an anti-tumor immune response. Additionally, we will discuss several non-central nervous system cancers where neoadjuvant immune checkpoint inhibition has been successful and compare this approach to what is currently being done in the treatment of malignant gliomas. We will also discuss why we believe neoadjuvant administration of immune checkpoint inhibitors may provide a survival benefit for brain tumor patients. We hope this manuscript will foster future studies aimed at exploring whether this approach may be beneficial for patients diagnosed with gliomas.